Mimetic Learning - Christoph Wulf (Stockholm University Press, 2008)
Mimetic learning, learning by imitation, constitutes one of the most important forms of learning. Mimetic learning does not, however, just denote mere imitation or copying: Rather, it is a process by which the act of relating to other persons and worlds in a mimetic way leads to an en-hancement of one's own world view, action, and behaviour. Mimetic learning is productive; it is related to the body, and it establishes a connection between the individual and the world as well as other persons; it creates practical knowledge, which is what makes it constitutive of social, artistic, and practical action. Mimetic learning is cultural learning, and as such it is crucial to teaching and education (Wulf, 2004; 2005).